Pragmatic Aspects of Derivatives Functioning in Fiction - Minasyan, Alla (Armenian Folia Anglistika, 2012)
The characteristics of the formation of derivatives, the compound nature of their structure provide ample opportunities for the realization of its purposes. Various transformations can take place inside derivates – dissolution of constituents and re-arrangement, fusions, use of a morpheme as an independent word, violation of the standards of the combinability of morphemes, repetition of the morphemes in derivatives, etc. These transformations take place in linguistic units that create word-forming stylistic devices beyond their traditional area of application.